Produtividade e teores foliares de nutrientes da soja em função de diferentes plantas de cobertura - Shirado, Evelyn Yumi Naste (2016)
In recent decades, the direct tillage system has been adopted by the majority of grain farmers in the savannas region; however, in this cultivation system, has been noted difficulties in defining what are the best species to compose the crop rotation system, in the autumn-winter period, aiming a higher production of grain and straw. The objective of this study was to evaluate the productivity and foliar content of soybeans nutrients due to different cover crops in the savannas region, leaf analysis of crops preceding and successor of soybeans, and chemical analysis of the soil in the layer from 0.0 to 10 cm in the years of 2013 and 2015, making a comparison of the effects on soil chemical properties, through the rotation/succession system during this period. The experiment was conducted in FAECA (UFGD), located in Dourados/MS, in a distroferric red latosol, in a randomized block design with four replications. Seven plots were analyzed, been the autumn/winter crops preceding the soy: fallow, corn, corn + brachiaria, turnip, niger, vetch + oats + turnip and vetch; and successors: fallow, corn, corn + brachiaria, safflower, ochroleuca crotalaria, vetch and turnip. It was evaluated in soybean the grains productivity and nutrient foliar content (N, P, K, Ca, Mg, Cu, Fe, Mn and Zn). In autumn/winter crops, preceding and succeeding soy, was evaluated the nutrient content in leaves (N, P, K, Ca, Mg and S). It was also evaluated the chemical changes in the soil in the layer 0.0 to 10 cm in the years of 2013 and 2016. The methodology that obtained the highest productivity was the one when the preceding crop to soy crop was the intercropping vetch + oats + turnip, totaling 3053.70kg.ha -1 . The intercrop vetch + oats + turnip, among the plant covers evaluated in this experiment, showed be the most suitable to precede soybeans. The turnip succeeding soybeans showed high contents for all studied nutrients. Among treatments, there were not statistical differences for foliar contents of soybean, with the exception of nitrogen and potassium. The average zinc levels are considered low. Even without correction in the soil, since 2009, the soil pH did not suffer big oscillation, and the soil maintained its fertility.